Healing the Healers: Adressing Occupational Stress and Promoting Well-Being Among Anaesthesiology and Reanimation Physicians in Türkiye - Elif Oral Ahıskalıoğlu; Miraç Selcen Özkal Yalin (Atatürk Üniversitesi Tıp Fakültesi Cerrahi Tıp Bilimleri Dergisi)
Objective: Anesthesiology and reanimation is a high-performance specialty where physicians are constantly exposed to stressors. This study primarily aims to evaluate the physical and mental health status of physicians working in anesthesiology and reanimation in Turkey, and to further identify the major occupational stress factors that could be eliminated by fatigue-management strategies.Methods: Our study was conducted through an online 63-item questionnaire. 115 anaesthesiologists working at various institutions in Türkiye were included. The questionnaire consists of multiple-choice and open-ended questions, designed with a 4-point Likert scale. The cumulative Likert scores for the responses were statistically evaluated, and further analyses were performed through comparisons among different groups of physicians with various descriptive characteristics.Results: 57.4% of physicians reported near-miss incidents caused by fatigue. Burnout levels were highest among trainees, followed by specialists, with faculty members experiencing the least burnout; physicians with children reported lower burnout, while female anaesthesiologists experienced more Imposter Syndrome symptoms. Hospital conditions for physician health were poorest in training and research hospitals and best in university hospitals, with a significant difference between the two (P=.004). Conclusion: Early recognition and treatment of the negative effects of occupational stress on anesthesiologists are crucial for improving patient safety and work performance. There is a need for more research in this field in Türkiye for raising awareness of burnout and fatigue amongst anaesthesiologists and hospital managements.